The Defects of Police Reform in Indonesia - Haripin, Muhamad; Siregar, Sarah Nuraini (RMPI-BRIN, 2016)
This paper discusses the development of the Indonesian National Police (POLRI) in undertaking internal reform, and its place within the democratic transition in Indonesia. This paper tries to enrich the on-going discussion on police and political dynamics, and to provide valuable insight into internal debates. The main challenges to advancing reform are identified, which are the politicization of the police and external obstruction.